Changes in the Shoreline of Costa Rica South Caribbean During the Period 2005–2016 - Barrantes Castillo, Gustavo (2021)
[Introduction]: Globally, 24 % of the planet's sandy beaches are eroding. In the case of Latin America, it is not a general problem, but it is severe in certain regions. On the Caribbean coast of Costa Rica, 11 critical points with intense erosion are reported. [Objective]: to analyze the changes in the coastline in the South Caribbean of Costa Rica, quantify the erosion and accretion processes, and understand the influence of the littoral currents on the sediment distribution. [Methodology]: It is based on the quantification of changes in the coastline for the period 2005-2016 through the DSAS extension, using the vegetation line on the coast as a proxy. [Results]: 54% of the coastline is stable, 23 % experience erosion, and 22 % accretion. There is a severe erosion process at the Limón airport, in the southeast of Westfalia, in Cahuita, Puerto Vargas, Manzanillo, and Gandoca. Beaches with significant accretion were located, such as Cieneguita to the north of the breakwater, Bananito beach, the beach near the Dixibre River, the beach between the mouth of the Estrella and Tuba rivers, and a small sector in Punta Cahuita. [Conclusions]: The southern Caribbean of Costa Rica experiences alternating erosion and accretion processes; the greatest changes are related to migration to the mouths of important river systems. Protected areas are among the most affected sites.